A crise financeira de 2008: uma reflexão a partir da teoria da fragilidade financeira de Hyman Minsky - Oliveira, Mayara Garcia de [UNESP] (2013)
This paper aims to use the theoretical framework developed by Hyman P. Minsky for understanding the concept of financial fragility observed in the capitalist system. It is intended to clarify the concept of intrinsic instability to which capitalism is subject, which is responsible for generating more economic cycles - periods of prosperity and crashes that affect global economies - particularly the one initiated in the United States in 2008. Thus, we made theoretical analysis of the theory of economic cycles and financial instability beyond historical reviews on the biggest financial crisis since the Great Depression